The Epizootiological and Epidemiologic Situation on Brucellosis in the Southern Federal District of the Russian Federation in 2006-2009 - G. I. Lyamkin; N. I. Tikhenko; E. A. Manin; S. V. Vilinskaya; S. I. Golovneva; D. V. Rusanova (Проблемы особо опасных инфекций, 2010)
Presented is the analysis of dynamics of brucellosis morbidity in people and animals. Evaluation of epizootiological and epidemiological situation on brucellosis in the Southern federal district of the Russian Federation for 2006-2009 is given. It is shown that unfavorable epidemic situation on brucellosis persists in the number of regions of the Southern federal district of RF that gives the basis to predict the preservation of morbidity at a high level.